1991
DOI: 10.1103/physrevlett.67.927
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen embedded in Ni: Production by incident atomic hydrogen and detection by high-resolution electron energy loss

Abstract: The vibrational modes of hydrogen embedded in a Ni crystal are shown to be detectable by highresolution electron-energy-loss spectroscopy and to be unambiguously distinguishable from the vibrational modes of adsorbed hydrogen on the basis of the dependence of the inelastic electron intensity on electron impact energy. The embedded hydrogen has a vibrational frequency of 800-850 cm"' and is observed to recombine and desorb as H2 between 180 and 220 K. The absorption of hydrogen into Ni(l 11) is achieved under U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
122
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(133 citation statements)
references
References 23 publications
11
122
0
Order By: Relevance
“…We posit that tunneling electrons propagating from the tip into the crystal (or vice versa at negative sample bias) scatter inelastically from hydrogen atoms in the bulk. This hypothesis is supported by the work of Ceyer and coworkers (31), in which high-resolution electron energy loss spectroscopy was used to detect the vibrational modes of H atoms embedded in a Ni crystal. From their spectra, they concluded that vibrational modes of H atoms in the bulk were unambiguously distinguishable from surface-bound H, and that these modes were excited by impact scattering of the electrons.…”
Section: Resultssupporting
confidence: 53%
“…We posit that tunneling electrons propagating from the tip into the crystal (or vice versa at negative sample bias) scatter inelastically from hydrogen atoms in the bulk. This hypothesis is supported by the work of Ceyer and coworkers (31), in which high-resolution electron energy loss spectroscopy was used to detect the vibrational modes of H atoms embedded in a Ni crystal. From their spectra, they concluded that vibrational modes of H atoms in the bulk were unambiguously distinguishable from surface-bound H, and that these modes were excited by impact scattering of the electrons.…”
Section: Resultssupporting
confidence: 53%
“…While for a long time carbon was considered a site blocker, Geoff Webb [78] suggested that it is the hydrogen directly connected with the carbon is the relevant species involved in hydrogenation. The traditional opinion that only surface hydrogen species participate in the hydrogenation process was also questioned by Ceyer and co-workers studying ethylene hydrogenation on Ni(111) [79]. More recently, other experimental and theoretical evidences for the important role of subsurface hydrogen were reported and it has been suggested that the carbonaceous species control the hydrogen distribution on and in the particle [80][81][82].…”
Section: Example #3: Olefin Hydrogenation: Nanoparticles Versus Singlmentioning
confidence: 94%
“…This metastable subsurface H can be prepared at low temperatures by exposure of the surface to atomic hydrogen followed by collision-induced recombinative desorption to remove the surface bound H under UHV conditions. [32][33][34] To explore the role of subsurface H (H b ) in CO 2 hydrogenation on Ni(111), we first studied CO 2 hydrogenation with surface H in the presence of subsurface H as a spectator. We then studied CO 2 hydrogenation with subsurface H as a reactant at a low coverage (2/9 ML) and a full ML coverage.…”
Section: Methodsmentioning
confidence: 99%